2018
DOI: 10.1111/pere.12228
|View full text |Cite
|
Sign up to set email alerts
|

Moral judgment toward relationship betrayals and those who commit them

Abstract: In three experimental studies (total N = 1,056), we examined moral judgments toward relationship betrayals, and how these judgments depended on whether characters and their actions were perceived to be pure and loyal compared to the level of harm caused. In Studies 1 and 2, the focus was on confessing a betrayal, whereas in Study 3, the focus was on the act of sexual infidelity. Perceptions of harm/care were inconsistently and less strongly associated with moral judgment toward the behavior or the character, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…An interesting finding of this study was that previous experience with infidelity does not affect the perception of extradyadic behavior as indicative of it. This could be due to the fact that the perception of extradyadic behavior could be influenced to a greater extent by social norms, because such behaviors tend to occur within a more collective and less situational context (e.g., infidelity may be less accepted at a social level; however, it is more tolerated within the relationship; Selterman and Koleva, 2015; Selterman et al, 2018). Future research could replicate these findings considering the role of social norms in the perception of extradyadic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding of this study was that previous experience with infidelity does not affect the perception of extradyadic behavior as indicative of it. This could be due to the fact that the perception of extradyadic behavior could be influenced to a greater extent by social norms, because such behaviors tend to occur within a more collective and less situational context (e.g., infidelity may be less accepted at a social level; however, it is more tolerated within the relationship; Selterman and Koleva, 2015; Selterman et al, 2018). Future research could replicate these findings considering the role of social norms in the perception of extradyadic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it remains an open question whether the present findings generalize to more severe transgressions within close relationships (see e.g., Selterman et al, 2018). Notably, some prior research found stronger favoritism of close (vs. distant) others for more (vs. less) severe transgressions (e.g., credit card fraud; Weidman et al, 2020), but did not include the self as a target (and transgressor).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 62%
“…To operationalize immoral achievements, we used a theoretical framework for three types of moral violations: care/harm, loyalty/betrayal, and purity/degradation. Previous research suggested that the perception of these particular categories negatively impacts interpersonal relationships (Selterman et al, 2018; Selterman & Koleva, 2015). We conducted a pilot study to develop and validate a set of capitalization disclosures, that is, brief success stories that individuals communicate with others (see Table 1).…”
Section: Studymentioning
confidence: 99%